Opening Space for Theoretical, Methodological, and Empirical Issues in Human-Machine Communication - Leopoldina Fortunati; Autumn P. Edwards (Human-Machine Communication Journal, 2020)
This journal offers a space dedicated to theorizing, researching empirically, and discussing human-machine communication (HMC), a new form of communication with digital interlocutors that has recently developed and has imposed the urgency to be analyzed and understood. There is the need to properly address the model of this specific communication as well as the roles, objectives, functions, experiences, practices, and identities of the interlocutors involved, both human and digital. Reading these seven articles is an advantageous intellectual exercise for entering this new field of research on Human-Machine Communication. The present volume contributes substantially both at theoretical and empirical levels by outlining this new field of research, giving new perspectives and models, and inspiring new paths of research.